2022
DOI: 10.1073/pnas.2200553119
|View full text |Cite
|
Sign up to set email alerts
|

A versatile fluorescence-quenched substrate for quantitative measurement of glucocerebrosidase activity within live cells

Abstract: Loss of activity of the lysosomal glycosidase β-glucocerebrosidase (GCase) causes the lysosomal storage disease Gaucher disease (GD) and has emerged as the greatest genetic risk factor for the development of both Parkinson disease (PD) and dementia with Lewy bodies. There is significant interest into how GCase dysfunction contributes to these diseases, however, progress toward a full understanding is complicated by presence of endogenous cellular factors that influence lysosomal GCase activity. Indeed, such fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…We employed a recently-described activity-based probe to measure lysosomal GCase activity (LysoFQ-GBA) that has superior signal to noise and retention in lysosomes compared to other probes tested to address this question (44). We confirmed that LysoFQ-GBA specifically detected GCase signal as no detectable signal was observed in GBA1 KO A549 cells (Fig.…”
Section: Endolysosomal Gcase Activity Glccer and Bmp Levels Are Contr...mentioning
confidence: 70%
See 3 more Smart Citations
“…We employed a recently-described activity-based probe to measure lysosomal GCase activity (LysoFQ-GBA) that has superior signal to noise and retention in lysosomes compared to other probes tested to address this question (44). We confirmed that LysoFQ-GBA specifically detected GCase signal as no detectable signal was observed in GBA1 KO A549 cells (Fig.…”
Section: Endolysosomal Gcase Activity Glccer and Bmp Levels Are Contr...mentioning
confidence: 70%
“…A clear understanding of the relationship between LRRK2 and lysosomal GCase activity has been hindered by limitations in existing methods to measure GCase activity with respect to sensitivity, selectivity, and spatial resolution. We employed a recently-described activity-based probe to measure lysosomal GCase activity (LysoFQ-GBA) that has superior signal to noise and retention in lysosomes compared to other probes tested to address this question (44). We confirmed that LysoFQ-GBA specifically detected GCase signal as no detectable signal was observed in GBA1 KO A549 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next exploited a GCase-specific fluorescence-quenched substrate LysoFQ-GBA 29 to measure increase in lysosomal GCase activity in neurons. Cell imaging revealed that treating Gba -deficient immortalised murine cortical neurons for 2 h with mGCase or mGCase-mBS could restore lysosomal GCase activity to WT levels.…”
Section: Resultsmentioning
confidence: 99%